Development and Validation of a Method for Quantification of 28 Psychotropic Drugs in Postmortem Blood Samples by Modified Micro-QuEChERS and LC–MS-MS. Issue 7 (30th September 2020) - Rodrigues, Taís B; Morais, Damila R; Gianvecchio, Victor A P; Aquino, Elvis M; Cunha, Ricardo L; Huestis, Marilyn A; Costa, Jose Luiz
Abstract: The development of new sample preparation alternatives in analytical toxicology leading to quick, effective, automated and environmentally friendly procedures is growing in importance. One of these alternatives is the QuEChERS, originally developed for the analysis of pesticide residues, producing cleaner extracts than liquid–liquid extraction, and easier separation of aqueous and organic phases. However, there are few published studies on the miniaturization of this technique for forensic toxicology, especially in postmortem analysis. We developed and validated a modified micro-QuEChERS and LC–MS-MS assay to quantify 16 antidepressants, 7 antipsychotics and 3 metabolites and semi-quantify norfluoxetine and norsertraline in postmortem blood. The calibration curve was linear from 1 to 500 ng/mL, achieved an r  > 0.99, with all standards quantifying within ±15% of target except ±20% at the limit of quantification of 1 ng/mL for 26 substances. The F test was applied to evaluate if the variance between replicates remained constant for all calibrators. Six weighting factors were analyzed (1/x, 1/x 2, 1/x 0, 5, 1/y, 1/y 2 and 1/y 0, 5 ), with the weighting factor with the lowest sum of residual regression errors (1/x 2 ) selected. No endogenous or exogenous interferences were observed. Method imprecision and bias were <19.0% and 19.7%, respectively. Advantages of this method include a low sample volume of 100 µL, simple but effective sample preparation and a rapid 8.5-min run time. The validated analytical method was successfully applied to the analysis of 100 authentic postmortem samples.